Investigating the Performance of Coded GSIM DCSK Communication Systems over Multipath Rayleigh Fading Channel - Ali Jaber Al-Askery; Fadhil Sahib Hasan; Ahmed A. Thabit (Journal of Communications Software and Systems, 2024)
Index modulation−based differential chaos shift keying (IM−DCSK) is a promising technique in wireless communication systems. Among all schemes, a Grouping Subcarrier Index Modulation DCSK (GSIM−DCSK) supports suit−coded modulation to improve bit error rate (BER) over a multipath Rayleigh fading channel, known as Coded GSIM−DCSK (CGSIM−DCSK) system. In the proposed method, all the index modulation bits are detected at the receiver side and then converted into a bipolar form to pass them through the channel decoder system along with the soft modulated bits. The results show that CGSIM−DCSK system with two schemes that are CGSIM−DCSK1 and CGSIM−DCSK2 are improved by the proposed coding techniques, with the LDPC code barely superior to the New Radio−Polar Code (NRPC). Furthermore, the performance of CGSIM−DCSK1 outperforms that of CGSIM−DCSK2 with lower information rate.